1994
DOI: 10.1152/ajpendo.1994.267.2.e316
|View full text |Cite
|
Sign up to set email alerts
|

beta-Adrenergic stimulation of skeletal muscle metabolism in relation to weight reduction in obese men

Abstract: (1994). beta-Adrenergic stimulation of skeletal muscle metabolism in relation to weight reduction in obese men. American Journal of Physiology, 267(2), E316-E322.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 3 publications
5
59
3
Order By: Relevance
“…It should be mentioned that there are major differences in catecholamine-induced lipolysis between depots (subcutaneous vs visceral and gluteofemoral) and also gender differences in body fat distribution. [43][44][45] Our data indicate that variability in codon 16 of the ADRB2 gene may contribute to a reduced in vivo b-adrenoceptor-mediated lipolysis and fat oxidation, [1][2][3][4] indicating that these blunted responses may be important primary factors in obesity.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…It should be mentioned that there are major differences in catecholamine-induced lipolysis between depots (subcutaneous vs visceral and gluteofemoral) and also gender differences in body fat distribution. [43][44][45] Our data indicate that variability in codon 16 of the ADRB2 gene may contribute to a reduced in vivo b-adrenoceptor-mediated lipolysis and fat oxidation, [1][2][3][4] indicating that these blunted responses may be important primary factors in obesity.…”
Section: Discussionmentioning
confidence: 70%
“…In vivo studies have shown that the development or maintenance of increased adipose tissue stores might be promoted by a blunted lipolytic response and fat oxidation after b-adrenergic stimulation or exercise in obese or obese type 2 diabetic subjects. [1][2][3][4] This blunted b-adrenoceptor-mediated lipolysis and fat oxidation persisted after weight reduction, indicating that this disturbance may be an early, even primary factor, in the development or maintenance of increased adipose stores. 1 There are indications that the blunted b-adrenergically mediated lipolysis in obesity may be related to an impaired function or a reduced number of adipocyte beta-2 (b 2 ) adrenoceptors.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A blunted fat oxidation response to b-androgenic stimulation may be a primary factor for increased fat stores and maintaining adipose tissue deposits following weight loss (Blaak et al, 1994b). UCP2 activity increases with increased blood lipid circulation.…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 99%
“…Impairments in the ability of the skeletal muscle to use FFA have also been reported in obese subjects during postabsorptive conditions (12) and ␤-adrenergic stimulation (13), suggesting that an impaired capacity to use fat may be one of the factors linking obesity to type 2 diabetes mellitus by promoting skeletal muscle insulin resistance and hyperglycemia. Additionally, persistent impairments in FFA utilization have been previously reported after weight loss in obese subjects (14,15), suggesting that these defects could also be primary to the obese state. This is consistent with the findings that a decreased reliance on lipid oxidation is a risk factor for weight gain (16) and for weight regain after weight loss (17).…”
mentioning
confidence: 91%